2001
DOI: 10.1103/physrevlett.87.065001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Intermittent Convection in the Edge of Magnetic Confinement Devices

Abstract: Probe measurements in the PISCES linear device indicate the presence of plasma radially far from where it is produced. We show that this is mainly caused by large-scale structures of plasma with high radial velocity. Data from the Tore Supra tokamak show striking similarities in the shape of these intermittent events as well as the fluctuation density probability distribution and frequency spectrum. The fact that intermittent, large-scale events are so similar in linear devices and tokamaks indicates the unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
191
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(206 citation statements)
references
References 18 publications
15
191
0
Order By: Relevance
“…11 Statistics of the turbulent transport were compared for both a linear plasma device and a tokamak. 12 It was shown that the probability distribution function (PDF) for the density fluctuations was skewed for positive fluctuations, which is consistent with the idea of large density structures propagating radially outward across the SOL. Moreover, the normalized PDF was very similar in the linear and toroidal devices, perhaps implying a common origin of the convective transport in both cases, despite the very different geometry and forces in the two devices.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…11 Statistics of the turbulent transport were compared for both a linear plasma device and a tokamak. 12 It was shown that the probability distribution function (PDF) for the density fluctuations was skewed for positive fluctuations, which is consistent with the idea of large density structures propagating radially outward across the SOL. Moreover, the normalized PDF was very similar in the linear and toroidal devices, perhaps implying a common origin of the convective transport in both cases, despite the very different geometry and forces in the two devices.…”
Section: Introductionsupporting
confidence: 70%
“…209 In linear devices the effect of magnetic curvature is absent yet some characteristics of blobs seem to be at least qualitatively similar to toroidal devices. 12,130,222 In some cases rotating plasma columns may provide centrifugal forces that mimic magnetic curvature effects. Although blobs are seen in poloidally symmetric linear devices, the introduction of a limiter into the plasma can also increase the intensity of blobs in its shadow.…”
Section: E Location and Structurementioning
confidence: 99%
“…Similar figures are valid also for tokamaks 2,3 and linear devices 4 . These intermittent events are nowadays associated to coherent structures moving into a background plasma.…”
Section: Introductionsupporting
confidence: 70%
“…Recent work in the JET tokamak 17 focused on the power spectra of the fluctuations, demonstrating that decay as 1/f was localized in the spectral region where intermittent ͑or bursty͒ transport is dominant and interpreting the result as an indication of closeness to instability thresholds. Therefore, the universality of intermittency and the concomitant fast convective transport has been established 6,18,19,8 for long. Additionally, there is an extensive body of work imaging the edge of various devices with fast cameras 20,21 which show that moving plasma filaments exist in the edge/SOL.…”
Section: Introductionmentioning
confidence: 99%